Evaluasi Pelaksanaan Program Pelatihan Kerja Unit Pelaksana Balai Besar Pelatihan Vokasi dan Produktifitas (BBPVP) Bandung - Arif Wijayanta; Pardjono Pardjono (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to assess the effectiveness of vocational training programs designed in accordance with industry needs by using a quantitative approach as the basis of analysis. Data collection was carried out through questionnaires distributed to training participants. The research population consisted of 64 training participants and 30 instructors, with 30 participants from the Electric Vehicle and Battery Pack class selected using purposive sampling, while all instructors were included as respondents. The effectiveness analysis was conducted by comparing the achievement levels of indicators in each component of the CIPP evaluation model (Context, Input, Process, Product). The results showed that the vocational training program at the Balai Besar Pelatihan Vokasi dan Produktivitas (BBPVP) Bandung demonstrated a high level of success. This is evidenced by participants’ interest, which reached 83.2%, and the alignment of the training with industry needs, which reached 98%. In addition, the quality of instructors and the availability of supporting facilities achieved a score of 79.03%, while the application of vocational education principles reached 82.14%, indicating that the training process was effective. Internal factors such as instructor competence, participant readiness, adequate facilities, and strong learning motivation contributed significantly to the training’s success. On the other hand, external factors such as the relevance of training materials to industry demands and the diverse backgrounds of participants, including both fresh graduates and experienced professionals, added value to the learning process. Overall, this study shows that the training program successfully met industry competency standards with a full achievement rate of 100%.